2011
DOI: 10.1007/s00264-011-1240-8
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic resonance imaging assessment of tibial tuberosity–trochlear groove distance: normal values for males and females

Abstract: The normal TTTG distance is 10 ± 1 mm with MRI being a reliable method of measurement. Literature supports a high degree of variability in reporting TTTG. This study establishes normal TTTG values, which will help in the assessment and treatment of patellofemoral disorders.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

10
117
3
4

Year Published

2013
2013
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 142 publications
(134 citation statements)
references
References 18 publications
10
117
3
4
Order By: Relevance
“…25 The cut-off point of 20 mm above which tibial tubercle osteotomy is indicated has been well accepted by most orthopaedic surgeons. [26][27][28][29][30] One study has shown that 18% of recurrent patellar dislocators had TT-TG distances of >20 mm. 31 For patients with significant trochlear dysplasia, trochleoplasty procedures have been advocated.…”
Section: Discussionmentioning
confidence: 99%
“…25 The cut-off point of 20 mm above which tibial tubercle osteotomy is indicated has been well accepted by most orthopaedic surgeons. [26][27][28][29][30] One study has shown that 18% of recurrent patellar dislocators had TT-TG distances of >20 mm. 31 For patients with significant trochlear dysplasia, trochleoplasty procedures have been advocated.…”
Section: Discussionmentioning
confidence: 99%
“…If the threshold value is taken as 20 mm in general, even with the same measurement techniques, different values of TT-TG have been given in literature as the threshold value of instability. 2,12,21 In a study by Park et al 21 of patients with patellar dislocation, the mean TT-TG distance was found to be 13 mm. Although this value was found to be statistically significantly higher than that of the group without instability in that study, it was reported to be a much lower value than that of previous studies.…”
Section: Discussionmentioning
confidence: 99%
“…3,4,11,12,15,16 Despite its extensive use, in cases where the TT-TG distance is <20 mm, it may not be able to explain other cases seen to have instability. 17,18 In the current study, it was attempted to answer the following questions: (1) Are metric parameters alone sufficient in the evaluation of patellar instability?…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Einen großen Einfluss auf das Patellatracking hat die TT-TG-Distanz, die physiologischerweise bei 10-15 mm liegt [23,27]. Eine TT-TG-Distanz von Eine Überkorrektur der TT-TG-Distanz auf neutrale oder sogar negative Werte führt im mittel-bis langfristigen Verlauf zu erheblichen retropatellaren Knorpelschäden [20] und ist zu vermeiden [11,27].…”
Section: Introductionunclassified